15-Day subchronic developmental toxicity studies of ursolic acid in rats. (October 2020) - Geerlofs, Lotte; He, Zhiyong; Xiao, Sa; Xiao, Zhi-Cheng
Abstract: Ursolic acid (UA) is a pentacyclic triterpenoid and has the characteristics to serve as a potential therapeutic agent for a range of disorders. However, detailed studies of the toxicity of UA, especially developmental toxicity of UA, are non-existing. The objective of this study was to determine the potential effects of UA on fetal development, adult reproductive system, and major organs. UA was dissolved in a 0.5% hydroxypropyl methylcellulose, 0.1% Tween 80 in Milli-Q Water solution. A 100, 300 or 1000 mg/kg/day dose of UA or a control vehicle was administered orally for 15 days to adults (Han Wistar) and pregnant females (Sprague-Dawley). The administration of UA in adults did not cause deaths or resulted in abnormal (reproductive) organ or body weights at the dose up to 1000 mg/kg/day. The administration of UA resulted in no significant toxicological changes in either maternal nor fetal subjects in terms of body weight, organ weights, food consumption, gross pathology, sex organs, maternal performances, and fetal performances. Together, this study indicates that oral dosing with UA is safe for adult rats and their offspring and the no observed adverse effect level for UA is likely higher than 1000 mg/kg/day. Highlights: No toxic effects were found after administration ursolic acid for 15 days in adults. No toxic effects were found in regard to fetal development after administration. The NOAEL is likely to be higher than 1000 mg/kg/day.